2002
DOI: 10.1007/pl00000307
|View full text |Cite
|
Sign up to set email alerts
|

B1 and B2 antagonists and bradykinin-induced blood flow in rat skin inflammation

Abstract: The results suggest that the involvement of the inducible B1 receptor in skin inflammation site is related to the site, duration and recurrence of the injury condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Our experiments clearly demonstrate that BK-induced PE in the rat knee is dose-dependent, and is specifically mediated by B2 subtype receptors, but not by B1, as indicated by antagonist blockade results. These results are in agreement with previous reports using similar animal models [ 3 , 35 , 36 ]. Early studies showed that B2 receptors are expressed in human synovial tissues [ 37 ] and that BK can be released from peripheral nerve terminals, as well as from peripheral tissues and cells including endothelial cells and neutrophils, upon nociceptive stimulation [ 37 40 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our experiments clearly demonstrate that BK-induced PE in the rat knee is dose-dependent, and is specifically mediated by B2 subtype receptors, but not by B1, as indicated by antagonist blockade results. These results are in agreement with previous reports using similar animal models [ 3 , 35 , 36 ]. Early studies showed that B2 receptors are expressed in human synovial tissues [ 37 ] and that BK can be released from peripheral nerve terminals, as well as from peripheral tissues and cells including endothelial cells and neutrophils, upon nociceptive stimulation [ 37 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…The expression of B1 could, however, be upregulated over a period of hours following a chronic exposure to noxious stimuli or inflammation factors [ 41 ]. Our experimental knee perfusion model was designed to analyze acute inflammation events within 1 h. Previous studies have reported that B1 receptors can be induced and activated in chronic inflammation [ 36 ]. Another possible reason is that our present study only used BK in its full-length peptide form, which is selective for the B2 receptors and much less selective for the B1 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…B1R is a non-internalizing receptor, and its long-term stimulation actually leads to an increased expression (23). Several studies point to B2R involvement in chronic inflammatory processes (24,25) and their improvement by receptor antagonist treatment (26)(27)(28)(29)(30). Reports of improvement after B2R antagonist treatment include experimental models of visceral and cutaneous inflammation (31), fatal cardiocirculatory breakdown in experimental pancreatitis (32), and antigen-induced arthritis in rabbits (33,34).…”
Section: Discussionmentioning
confidence: 99%